Projectile Motion Modeling with Linear Resistance - Hidayat, Rusli (Jurusan Matematika FMIPA Universitas Jember, 2016)
When the projectile is shot into the air, the main force affecting the motion of projectile, other than gravity, is air resistance. This slowing down force is drag force, and it acts in a direction opposite to the velocity of the projectile. For the projectiles moving through the air at relatively low speeds, however, the drag force is proportional to the speed and so is called linear. The aim of this paper is to discuss the projectile motion by considering air friction as linear resistance. The results obtained show that the projectile motion model with linear resistance is more complex in formulating maximum height and range than the model without air friction force.